2020
DOI: 10.3389/fpls.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of TOR Kinase in Plant Development

Abstract: TARGET OF RAPAMYCIN (TOR) kinase has been recognised as a key developmental regulator in both plants and animals. Despite their distinct developmental programmes, all eukaryotes studied possess a functional TOR kinase, which integrates environmental and nutrient signals to direct growth and development. This is particularly important in plants, as they are sessile and must sense and respond to external signals to coordinate multicellular growth appropriately. Thus, the investigation of TOR is essential for pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…The complex of TOR protein kinases are potent cell growth regulators in all eukaryotes. For plants, RAPTOR1 is especially considered to be the most crucial for promoting cell expansion and coordinating multicellular growth in response to external signals, such as nutrients and PGRs (Anderson and Hanson 2005 ; McCready et al 2020 ). In the present study, higher expression (according to RNA-seq analysis) of the RAPTOR1 gene was found in PT–SH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex of TOR protein kinases are potent cell growth regulators in all eukaryotes. For plants, RAPTOR1 is especially considered to be the most crucial for promoting cell expansion and coordinating multicellular growth in response to external signals, such as nutrients and PGRs (Anderson and Hanson 2005 ; McCready et al 2020 ). In the present study, higher expression (according to RNA-seq analysis) of the RAPTOR1 gene was found in PT–SH.…”
Section: Discussionmentioning
confidence: 99%
“…Lower expression of this gene, though still higher than in the leaves of regenerated plants, was noted in both the OC and PT. The high expression of RAPTOR1 , called the “master regulator” (McCready et al 2020 ) may indicate the high activity of developmental processes which take place in PT–SH. Contradictory results have been reported for the callus and regenerated shoots in tomato plants (Kumari et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…RBR and TOR connect metabolic and auxin signaling in cell cycle regulation. TOR has been reported to regulate AR induction in Arabidopsis and potato ( Deng et al, 2017 ) and participate in meristem size regulation by controlling cell proliferation ( McCready et al, 2020 ). In addition, TOR inhibition has been reported to produce a decrease of DNA methylation affecting genes involved in hormone signaling, suggesting a role in chromatin remodeling ( Zhu et al, 2020 ).…”
Section: Identifying Molecular Checkpoints For Adventitious Rooting Cmentioning
confidence: 99%
“…As in non-photosynthetic eukaryotes, TOR is involved in a multitude of processes in plants, including plant organ initiation, growth and patterning, translation, transcription, cell cycle control, and autophagy [ 75 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 ]. In the following sections, we discuss upstream and downstream TOR-autophagy signaling network components in photosynthetic organisms, including algae and land plants.…”
Section: Tor Signaling In Photosynthetic Organismsmentioning
confidence: 99%